Christmas Echoes at Paschaltide - Cabaniss, Allen (New Testament studies, 1962)
In one of the oldest strata of Gospel tradition and within the brief compass of three verses (Mark xv. 43, 46, 47), there is an intriguing possibility that we have in the account of Christ's entombment an echo of his birth-story.